REAL WORLD EFFICACY OF NEVIBOLOL ACCORDING TO VARIOUS PRESCRIPTION PATTERNS IN THE OPEN, NON-CONTROLLED, PROSPECTIVE, MULTICENTER OBSERVATIONAL STUDY IN KOREA (BENEFIT-KOREA). (June 2018) - Shin, J.; Cho, B.; Choi, Y.; Hong, G.; Yoon, H.; Shim, W.; Jang, J.; Ko, Y.; Jeon, D.; Cha, D.; Kim, S.; Bae, W.; et al.
Abstract: Objective: Although the role of beta blocker in major hypertension guideline is limited, the role of vasodilating beta blocker is suggested to be different from the conventional beta blocker. Despite of many small sized studies for the pharmacological properties, there are few large sized real world data for blood pressure (BP) lowering efficacy of nevibolol in hypertension patients in Asia. Design and method: In the open, non-controlled, prospective, multicenter observational study to identify BEnefits after 24 weeks of NEvibolol administration For essential hypertensIon patients wiTH various co-morbidities and treatment environments in KOREA (BENEFIT-KOREA), 3011 patients was enrolled and 2571 patients (85.3%) completed 24 week follow up. The efficacy of nevibolol was measured according to four prescription patterns, i.e., de novo therapy (n = 279), single drug switching (n = 257), switching for combination therapy (n = 978), and add-on therapy (n = 1057). Results: Age was 63.5 ± 12.9. Female was 40.4% and the elderly aged > 65 was 52.7%. Dyslipidemia, obesity, and diabetes mellitus were noted in 50.5%, 37.4%, and 28.9%. Co-morbidity was noted in 89.1% and majority was ischemic heart disease. Concomitant medication rate for calcium antagonist, ARB/ACEI, diuretics were 54.3%, 53.5/9.2%, and 23.7%. Median dosage of nevobolol was 5 mg. For de novo therapy, BPs decreased from 142.4/84.9 mmHg to 127.9/75.1 mmHg (−13.9/−9.5 mmHg, p < 0.0001). For single drug switching group, BPs decreased from 134.3/78.7 mmHg to 127.1/75.3 mmHg (−7.5/−3.6 mmHg, p < 0.0001). For switching for combination therapy group, BPs decreased from 137.8/80.1 mmHg to 131.6/76.6 mmHg (−6.4/−3.6 mmHg, p < 0.0001). For add-on therapy group, BPs decreased from 146.0/85.5 mmHg to 130.9/76.3 mmHg (−15.0/−9.1 mmHg, p < 0.0001). Adverse drug reaction was noted in 1.2%. Conclusions: Nevibolol was demonstrated to be a comparable drug for switching in single or combination therapies and to be an effective BP lowering drug for de novo or add-on therapies in a real world Asian hypertension patient with aging, cardiovascular risk factors, and co-morbidities.